The possible role of molecular mimicry in SARS-CoV-2-mediated autoimmunity: an immunobiochemical basis - Kovačić, Dženan; Jotanović, Jovana; Laković, Jasmina (Journal of Medical Science, 2021)
Coronavirus Disease 2019 (COVID-19), caused by the novel Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), persists as a threat to global health and continues to be a rapidly evolving condition. Although COVID19 is negatively correlated with the existing comorbidities in terms of the clinical outcome, the ability of SARS-CoV-2 to mediate the novel, or to exacerbate the existing autoimmune conditions, has generated considerable interest, due to its potential implications both with regard to patients suffering from autoimmune conditions, as well as to the long-term consequences of the disease. However, although molecular mimicry has been postulated as a potential causative factor in post-COVID19 autoimmunity and multi-organ damage, a substantial body of research needs to emerge in order to achieve a more definitive conclusion. We investigated the possibility of SARS-CoV-2 peptide sequences behaving as molecular mimics with a potential to trigger an autoimmune response. Thus, on the basis of analysis in silico, we were able to develop a plausible case for the molecular mimicry as a potential aetiological mechanism of SARS-CoV-2-mediated autoimmunity, both in a multi-organ damage context or outside of the viral phase of infection. Interestingly, this is the first time that the peptide sequence of MACROD1 has been implicated in the COVID-19 autoimmunity. Additionally, we also confirm that PARP9 and PARP14 may be involved in the process.